Observation of low frequency electrostatic coherent oscillation in the proximity of the density limit in the TJ-II stellarator. (19th November 2021) - Fernández-Ruiz, D.; Losada, U.; Ochando, M.A.; Liu, B.; Hidalgo, C.; the TJ-II Team,
Abstract: Turbulence self-regulation mechanisms are widely believed to be partially governed by the non-linear interplay between turbulence and large-scale plasma flows. In this paper, we employ floating potential data recorded via Langmuir probes to study the evolution of long-range correlated structures in plasmas near the operational density limit of the TJ-II stellarator. The results point towards the presence and amplification of low frequency, coherent, global fluctuations with similar properties to those of the zonal flows in the vicinity of this limit.